Social active avoidance behavior unaffected by optogenetic silencing of anterior cingulate cortex and provides model driven practices for behavioral data analysis - Erickson, Greg R. (Kansas State University, 2023)
Social transmission of fear is an essential neurobiological and behavioral function in social animals that allows for survival of environmental threat and danger. This study examines the role of the anterior cingulate cortex (ACC) in observationally conditioned freezing behavior during a social active avoidance task, using an optogenetic manipulation. Rodents were intracranially injected with either a target (ArchT) or control (eYFP) adeno-associated virus (AAV) and implanted with fiber optic probes in their ACC. Following recovery and virus maturation, rodents trained for 10 days and were then tested using optogenetic photoinhibition of the ACC across two days, counter-balanced across solo and social context. Our findings concurred with prior research, as inhibition of ACC function after acquisition of socially transmitted fear did not reduce freezing behavior. Following experimental data collection, distributional analysis emphasized the necessity of transforming non-normal data to ensure accurate statistical models, with our data revealing significant results in non-transformed data disappearing upon normalization. Additionally, test-retest reliability was affirmed for the dependent measures of time freezing and lever pressing, while the measure of time on platform displayed weaker reliability. An important analytical revelation was the risk of overlooking interaction analysis in behavioral neuroscience data modeling. The study underscores the significance of interaction modeling in behavioral neuroscience data analysis, as improper analysis of the study data again resulted in misleading conclusions. We advocate for rigorous analytical practices in neuroscience and emphasize that proper data modeling is indispensable for producing reliable research outcomes. Future endeavors should further investigate ACC's role in observationally conditioned fear, potentially by inactivating the ACC during training phases to corroborate findings from preceding studies.
Keywords: Neuroscience; Optogenetics; Anterior cingulate cortex; Model selection; Behavioral; Rodents